Pattern of Occurrence of Ocular Injuries and their Forensic Aspects - Timsinha, Sidarth; Kar, Suvarna Manjari; Ranjeetkar, Malshree (Birat journal of health sciences, 2019)
Introduction: All penetrating or non-penetrating intentional ocular trauma causing loss of an organ or part of an organ and which have as a consequence the facial disfigurement or post trauma sequelae formation have forensic implications. Objectives: To study the pattern of ocular injuries its forensic implications and meticulous documentation in ocular medicolegal cases. Methodology: This hospital based cross sectional study was carried out by Forensic medicine personnel in Department of Ophthalmology and Emergency Department of Manipal Teaching Hospital Pokhara, Nepal. A total of 251 cases of ocular injury constituted the sample size. Cases were analyzed according to age, sex, type of trauma, causative agent, and manner of injury and ocular injuries having any medicolegal value. All data was evaluated and relevant information were extracted and entered into a database. Results: Male subjects 174 (69.32%) were more susceptible to ocular injuries and age group 21-30 years 66 (26.3%) were more predisposed to ocular injuries. The commonest cause of ocular trauma was due to fall on blunt objects 42(16.73%). The most common site of injury was cornea 120(47.81%) and corneal abrasion 65(54.16) was the most common ocular finding. Accidental manner of injury was observed in majority of the cases 230 (91.60%). Ocular injuries sustained were all simple in nature 251(100%) as a result no fatality was observed following ocular injury. Conclusion: Proper history taking and methodical documentation of injuries not only assist in diagnosis and management of the patient but also holds an evidentiary value in medico legal cases.